Theaetetus2 *: Expectations, disappointments and fulfilments - Richardt Strøbech, Ralf (Peripeti, 2021)
This article examines what constitutes knowledge in art, law, journalism, and more specifically in artistic research. Taking its formal departure in the famous Theaetetus-dialogue by Plato, the article employs three different approaches to examine conceptions of knowledge. The first part, Knowledge is perception, examines narratives and imaginary qualities of key figures involved in huge money laundering scandals and other financial crimes in Denmark in 2018. The second part, Knowledge is true belief, elaborates on the concept of knowledge in art, law, and journalism through a series of abstracted dialogues-turned-monologues based on the material presented in the first part. It aims at a better understanding of how Facts, Truth, Time, Relevance, and Knowledge are conceptualized in the three disciplines. Finally, the third part, Knowledge is true belief with an account, elaborates on the core belief underpinning this artistic research project, using a dialogical form with footnotes. This core position is that knowledge in artistic research is based on the merging of knowledge and account, and functions through a specific type of extended discourse which, as conceptualized by Paul Ricoeur, is at once poetic and epistemologically productive imagination.